Enhancing Food Security in Afghanistan : Private Markets and Public Policy Options - World Bank (Washington, DC, 2014)
This report analyzes some key aspects of food security, namely production, trade, markets and food aid at the national level, and consumption at the household level. In doing so it aspires to make a contribution to the on-going work in Afghanistan regarding the attainment of the poverty and hunger Millennium Development Goal. The major findings of the report can be summarized as follows: Food security (at the national level) does not necessarily require national self-sufficiency in wheat or other food staples, as long as the country has access to international markets. Rather, diversification into legal high-value crops and livestock products may be the most effective means of increasing food security, by generating foreign exchange and raising the incomes and purchasing power of the rural poor. In spite of very difficult conditions, wheat markets in Afghanistan have performed fairly well and private sector international trade has helped to stabilize supply and prices. Therefore, further developing the infrastructure and institutions to support wheat markets and facilitating private sector trade is called for and will enhance food security. At the household level, food insecurity in Afghanistan is largely caused by inadequate access to food resulting from low household incomes. For most of Afghanistan, where availability of food is not a constraint, increasing cash incomes is the more efficient means of enhancing food security of the poor. Development of both private and public capacity for data collection and analysis is a high priority for effective formulation, assessment and implementation of food policies.